MENGUDUSKAN DIMENSI TEOLOGI MASJID: MENGHINDARI INTERVENSI POLITIK PRAKTIS DEMI MENJAGA KEMURNIAN MASJID DI INDONESIA - Bangun, Immanuel Cristwo (UIN Sumatera Utara Medan, 2025)
Mosques, as places of worship and sanctification, transcend its role as mere places of worship. This study examines the impact of practical political intervention on the theological and sanctity dimensions of mosques in Indonesia. This is a qualitative study oriented towards literature review. The focus of the study is to understand how political intervention can affect the function and image of mosques as centres of religious activity. It was found that mosques do not only function from a theological perspective but also as centres for social activities. However, the sanctity of the theological dimension of mosques is often threatened by practical political interventions that can lead to deviations from the primary purpose of mosques as sacred places. Practical politics manifests itself in efforts to control politics through mosques, such as covert campaigns through religious activities, social assistance, and political mobilisation within Muslim communities. The shift in the function of mosques to become places of practical politics is a worrying phenomenon, obscuring the main purpose of mosques as sacred places and centres of spirituality for Muslims. Therefore, the politicisation of mosques in Indonesia requires a more prudent and sensitive understanding, particularly to preserve the sanctity of mosques as pure entities, free from political interference that could undermine social harmony and diminish the sacredness of religion.